PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA TINDAK PIDANA MENYEBABKAN KEBAKARAN DALAM PUTUSAN NOMOR: 51/Pid.B/2021/PN Jkt.Sel - Muhammad Rafi Arkan; Heri Hartanto (Verstek, 2026)
This study analyzes the alignment of judicial considerations in deciding criminal cases related to causing fires, as outlined in Decision Number 51/Pid.B/2021/PN Jkt.Sel, with Article 183 of the Indonesian Criminal Procedure Code (KUHAP). This research employs a normative legal approach with a prescriptive and applied nature. The methodology used is a case approach. The types of legal materials utilized include primary and secondary legal materials. The data collection technique employed is library research. The legal material analysis technique used is syllogistic deduction. The findings of this study indicate that the judicial considerations in deciding the criminal case of causing fires in Decision Number 51/Pid.B/2021/PN Jkt.Sel are consistent with Article 183 of KUHAP.